Investigation of the effect of selected edible and medicinal plants on in-vitro blood coagulation profile: DOI: 10.48129/kjs.15505 - fathy, hoda; Mahrous, Rahma; Abu EL-Khair, Rasha; Omar, Abdallah; Ibrahim, Reham (Kuwait Journal of Science, 2022)
Anticoagulation therapy represents a mainstay of treatment and prevention of cardiovascular diseases which are the leading causes of mortality worldwide. In addition, several case reports of spontaneous bleeding occurred linking the consumption of many dietary supplements during treatment with anticoagulants or in postoperative patients. This prompted this study which is conducted on selected Egyptian plants to highlight their effect on blood coagulation profile using Prothrombin time (PT) and activated partial thromboplastin time (aPTT) tests. Some of these plants showed interesting results that need more in-depth evaluation of their anticoagulant activity as Hibiscus sabdarifa calyx extract for its effect on PT. In addition, extracts of Trifolium alexandrinum aerial parts and Pimpinella anismum fruit were proved to affect aPTT.Post operative or cardiovascular patients using herbal supplements should be cautioned about food-drug or herb-drug interactions and to adjust their herbal medication regimen before surgery.